Anthropometric and physical fitness profiles of Kelantanese intellectually disabled population - Mojiin, Willince (2024)
Intellectual disability (ID) is defined by the person that has a presence of incomplete or arrested mental development. Adults with ID typically reported to be overweight and obese and demonstrate poor level in physical fitness due to inactive lifestyle. The aim of this study is to identify the anthropometric measurement and physical fitness profile in adults with ID in Kelantan. This study also assessed the correlation of anthropometric and body composition on selected physical fitness performance assessed by medicine ball throw, standing long jump, static balance, 505 agility, and 20-m sprint test. Secondly, to predict the best predictors that can significantly contribute to physical fitness performance in term of explosive strength, balance, agility and speed. The fitness test batteries in this study were adapted from Inspire i-talent manual which developed by National Institute of Malaysia. A total of 124 adults with ID in Kelantan, 70 males and 54 females were recruited in this study. Anthropometric components (standing height, sitting height and arm span) were measured by using stadiometer and measuring tape while body composition such as body weight, fat free mass, fat percentage and body mass index (BMI) were recorded by using Bioelectrical Impedance Analysis (BIA). Adults with ID in this study are considered to be overweight. The higher BMI value was found in females (26.4 ± 6.6 kg/m2) than in males (22.7 ± 5.8kg/m2). In addition, physical fitness level in adult with ID in this study is considered to be generally poor, male participants performed better than female except in 505 agility test. Pearson correlation revealed that anthropometric parameters showed significant correlation with balance, lower and upper body power, agility, and speed Nevertheless, stepwise regression analysis revealed that agility test (R= 0.859, R2= 0.738, F= 6.136, p= 0.015) can be predicted by 20-meter sprint, standing long jump, and sitting height values. Besides, 505 agility test and sitting height were found to be strong predictor of 20-meter sprint (R= 0.839, R2= 0.705, F= 9.259, p=0.003). On the other hand, lower limb explosive strength variable (R= 0.864, R2= 0.747, F= 34,947, p<0.05) can be anticipated from medicine ball throw, fat percentage and 505 agility test values. In addition, for upper body explosive strength (R= 0.863, R2= 0.745, F= 4.223, p= 0.042) it can be forecasted from standing long jump, body weight, gender, static balance, and arm span values. Lastly, standing long jump and 505 agility test could be main predictor of static balance (R= 0.597, R2= 0.356, F= 6,586, p= 0.011). From these regression analysis findings, a few regression equations have been developed to predict agility, speed, explosive strength in both lower and upper body, and balance among intellectually disabled persons. Therefore, exercise intervention should be implemented to improve their general physical fitness level and to manage their weight to lower the rate of being overweight and obesity among intellectually disabled people.